Riparian buffers mitigate downstream effects of clear-cutting on instream metabolic rates - Myrstener, Maria; Lidberg, William; Kuglerova, Lenka (ACADEMIC PRESS LTD- ELSEVIER SCIENCE LTD, 2025)
Clear-cutting of forests with little or no regard for riparian buffers alters the local abiotic habitat of streams within and downstream of clear-cuts by increasing temperature, incident light, suspended sediments and resource inputs such as carbon and inorganic nutrients. It is also well documented that streams with narrow or non-existent riparian buffers affect local stream ecosystem processes. Here, we ask whether ecosystem processes can also be affected downstream of clear-cuts. We tested this in nine headwater streams that run through recently harvested clear-cuts (1-6 years ago) with varying buffer widths (= 15 m) in northern Sweden. We compared biofilm (periphytic algal and bacterial mats) and whole stream metabolic rates in stream reaches situated upstream of the clear-cuts, in the clear-cuts and downstream of the clear-cuts. We found that biofilm gross primary productivity (GPP) in streams with thin buffers (15 m) could mitigate these longitudinal changes for both biofilm and whole stream metabolism, except in one stream that was dominated by fine sediments. Importantly, the magnitude of downstream propagation in biofilm GPP was related to the magnitude of responses in the clear-cut, which in turn was driven by nutrient concentrations. To upscale the potential magnitude of clear-cutting in Sweden, we estimated that nearly 6 % (or 57,400 km) of the total forested stream length is situated within and 100 m downstream of clear-cuts that were harvested 1-6 years ago. Based on this study, we conclude that clear-cut effects on stream ecosystem processes are not only local, but can also be propagated to downstream recipient waters if riparian buffer width in the clear-cut is less than 15 m.